Observation of A White-bellied Sea-Eagle Icthyophaga leucogaster (Accipitriformes: Accipitridae) Preying on A Jellyfish (Cnidaria: Medusozoa) - Agus Prabowo; Henni Martini; Deni Mulyana; Reynaldi Sastra; Pormansyah; Muhammad Iqbal (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2026)
The White-bellied Sea-Eagle Icthyophaga leucogaster is a widespread Indo-Pacific raptor known for its predominantly piscivorous diet and opportunistic foraging behavior. Here, we report an unusual feeding observation of a juvenile I. leucogaster preying on a jellyfish at the mouth of the Sembilang River, South Sumatra, Indonesia, on 20 February 2018, at approximately 11:00 hrs. The eagle was observed lifting the jellyfish from the water surface and transporting it in its talons while in flight to a nearby perch. Jellyfish are rarely reported as prey for raptors and are generally regarded as having low nutritional value; however, their high visibility and ease of capture during periods of abundance may provide short-term energetic gains. This observation broadens current knowledge of the dietary range of I. leucogaster and underscores the species’ behavioral flexibility in exploiting unconventional prey resources.